PENETAPAN KADAR LOGAM Fe PADA BERAS MENGGUNAKAN SPEKTROFOTOMETRI SERAPAN ATOM - Ramadani, Regina Citra (DE FACTO : Journal Of International Multidisciplinary Science, 2024)
Indonesian society has a very high dependence on rice. The consumption level of rice reaches 139 kg/capita per year, this figure is higher than other countries such as Japan which has a consumption rate of 45 kg, Malaysia 80 kg, and Thailand 90 kg per year. This study aims to determine the level of Fe metal in rice using atomic absorption spectrophotometer instrument. The Fe content of the rice sample which was done in duplo was obtained at 12.84 mg/kg. This research uses an Inductive Approach where this research often begins with data collection without an initial hypothesis, and theories or generalizations arise from the analysis of the data obtained. The results of the levels of Fe metal in rice use a calibration curve which states the relationship between the levels of working solutions including blanks with a proportional response. Heavy metal Fe in rice tested in duplicates is not suitable for consumption because it exceeds the threshold allowed by the Decree of the Indonesian Minister of Health No. 492 of 2010. According to the regulation, Fe metal that does not exceed the threshold is 0.3 mg/kg.